Posted by **kyle** on Tuesday, December 4, 2012 at 11:03pm.

solve each inequalitiy

y+ (-5) > -6

## Answer This Question

## Related Questions

- maths - solve quadiratic inequalitiy using product propertise 6xsq -x+3<5xsq...
- Math - We have an important chemsitry test due and I want to make sure that I do...
- English - 1. He can not solve the math problem. 2. He cannot solve the math ...
- MATH PLEASEEEEE - I have a question, if f(x)=x/2 and g(x)=3x+1 find: a) (f+g)(x...
- math - actually, in a addition to the question i posted a few minutes ago, can ...
- English - I'm worried about my math. 1. Why don't you buy a math self- teaching ...
- Math - Solve by eliminnation methods 2x-4y=5 2x-4y=6 solve the system by ...
- MATH PLEASE HELP! - Solve each system 3x+2y= -2 9x- y= -6 I know how to solve ...
- Math - Solve for S: r^2s-5s=7. Solve for b: L= 4a^2b. I'm confused about how to ...
- Alebra - Solve 5m - 8 > 12 Solve 12 - 3a > 18 Solve 5m - 4 < 2m + 11 ...

More Related Questions